2005
DOI: 10.1097/01.gim.0000177530.55043.c1
|View full text |Cite
|
Sign up to set email alerts
|

NQO1, MPO, and the risk of lung cancer: A HuGE review

Abstract: The aim of this study is to summarize the available molecular epidemiologic studies of lung cancer and metabolic genes, such as NAD(P)H quinone reductase 1 (NQO1) and myeloperoxidase (MPO). NQO1 plays a dual role in the detoxification and activation of procarcinogens whereas MPO has Phase I activity by converting lipophilic carcinogens into hydrophilic forms. Variant genotypes of both NQO1 Pro187 Ser and MPO G-463A polymorphisms may be related to low enzyme activity. The Pro/Ser and Ser/Ser genotypes combined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
59
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 122 publications
5
59
1
3
Order By: Relevance
“…Moreover NQO1, NAT2 and several other genes have been reported as new susceptible genes of lung cancer (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). The present review focuses on new candidates, then examines all Japanese references by meta-analysis on susceptible genes over the past 20 years, and finally discusses whether new candidates and changing trend in Japan could be caused by environmental change.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover NQO1, NAT2 and several other genes have been reported as new susceptible genes of lung cancer (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). The present review focuses on new candidates, then examines all Japanese references by meta-analysis on susceptible genes over the past 20 years, and finally discusses whether new candidates and changing trend in Japan could be caused by environmental change.…”
Section: Introductionmentioning
confidence: 99%
“…This genetic susceptibility may derive from inherited polymorphisms in genes involved in the metabolism of xenobiotic chemical carcinogens (Shields et al, 2000;Shah et al, 2008). Results from published studies have shown that the variations of drug-metabolizing enzymes including cytochrome P450 (CYP), microsomal epoxide hydrolase 1 (EPHX1), glutathione S-transferase (GST), NAD(P) H quinone oxidoreductase 1 (NQO1), myeloperoxidase (MPO) and arylamine N-acetyltransferases (NATs) were associated with the sensitivity of lung cancer (Kiyohara et al, 2005;Agundez, 2008;Liu et al, 2013;Wang et al, 2013;Zhou et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Os dois autores sugeriram a utilização destes polimorfismos como marcadores de suscetibilidade individual ao benzeno . (Piedrafita et al, 1996;Williams, 2001;Kiyohara et al, 2005). A frequência do alelo A no gene MPO varia em cada população, tendo sido descrita em 23,4% dos Caucasianos e 14,4% dos asiáticos (Kiyohara et al, 2005).…”
Section: B Cunclassified
“…(Piedrafita et al, 1996;Williams, 2001;Kiyohara et al, 2005). A frequência do alelo A no gene MPO varia em cada população, tendo sido descrita em 23,4% dos Caucasianos e 14,4% dos asiáticos (Kiyohara et al, 2005). O genótipo variante de MPO 463 G > A tem sido associado ao risco reduzido de se desenvolver leucemia aguda, capacidade que é frequentemente atribuída à ativação diminuída dos carcinógenos por esta variante (Zhang et al, 2007).…”
Section: B Cunclassified
See 1 more Smart Citation